Mechanical mechanism of in situ stress ratio limit and its evolution simulation - Chen, Yifei; Wang, Yongjian; Huang, Fuqiong; Ma, Long; Yang, Changyi; Shi, Haoyu (Frontiers in Earth Science, 2022)
According to the Mohr Coulomb criterion, it is found that when the ratio of principal stress (the ratio of maximum principal stress to minimum principal stress) of crustal rock mass in a certain environment exceeds the critical value, the rock mass will change from elastic state to plastic state. This critical value is the extreme limit of principal stress ratio, which is related to the cohesion and internal friction angle of rock mass, and the limit of principal stress ratio in the shallow part is discrete; Because the principal stress of deep rock mass is large, the ratio limit is mainly related to the internal friction angle. The calculation results show that the principal stress ratio of deep rock mass is stable in a small range; By comparing and analyzing 574 groups of measured data, it is found that all the measured principal stress ratios are within the limit range of the theoretical ratio, which also shows the characteristics of shallow dispersion and deep stability, indicating that the theoretical analysis and the measured results are consistent with each other. In order to show the change process of in-situ stress, a numerical model fitting plate motion is established, and the limits of principal stress ratio in five periods in the past 500000 years are compared. The results show that the maximum principal stress at measuring points at different depths shows a change law of "first increasing and then stabilizing". In areas close to or exceeding the principal stress ratio, high shear strain zones appear in rock mass, and the stress is released in the form of plastic failure or shear dislocation, Make the main stress ratio finally stable between 6.0-8.0. Therefore, it is easy to judge the stability of regional strata by using the ratio of principal stress，the area with small ratio of principal stress belongs to the area with good stability, and when the ratio of principal stress is close to the limit of ratio, it is an unstable area. The measured data show that the area with high ratio of principal stress is often the recent seismic activity area.